To determine the efficacy and safety of acetic acid gel in comparison to silver sulfadiazine cream in patients suffering from second-degree burns - Chandrashekar Chalwade; Mangesh Kundlik Pawar; Abhijeet Sawant (Wolters Kluwer Medknow Publications, 2021)
Acetic acid solution is effective in healing of chronic wounds by its ability to eradicate biofilms. One percent silver sulfadiazine (SSD) cream is the commonly used topical antimicrobial agent in burn wound care. In our study, we compared the efficacy and safety of 1% acetic acid gel with 1% SSD in partial-thickness burn wound with <20% total body surface area. Context: Bacterial colonization of burn wounds results in delayed wound healing. SSD is commonly used as a topical antibiotic in the second degree and third-degree burn wounds. The acetic acid solution is found to be clinically effective against the eradication of mature or chronic biofilm.[6] We have used 1% acetic acid gel as an anti-microbial dressing for acute burn wounds and compared it with 1% SSD. Aims: To evaluate the efficacy and safety of acetic acid gel with SSD cream in patients with second-degree burn wounds involving up to 20% of total body surface area. Outcome parameters evaluated were Wound healing (BWAT score and status as on Day 21), Pain (VAS score), Healing quality (VSS score at 1 and 3 months) and adverse effects if any. Settings and Design: The study was conducted in the burn department affiliated with a tertiary care centre. It is a prospective randomized, investigator-initiated open-label case-control study. Inclusion criteria 1. Males and females between the ages of 18 and 65 years 2. Second-degree burn involving total body surface area up to 20% at 48 h of burn injury. Exclusion criteria1.Patients with pre-existing comorbidities. Uncontrolled diabetes Mellitus. Renal insufficiency.2. Patients with known keloid tendency3.Patients with electrical burn4.Patients with inhalation burn. Patients were included in the study in accordance with mentioned inclusion and exclusion criteria. Informed consent was obtained from all patients. All procedures contributing to this work comply with the ethical standards of the relevant national and institutional guidelines on human experimentation and with the Helsinki Declaration of 1975, as revised in 2008. The study group received 1% Acetic acid gel while the control group received 1% SSD cream for antimicrobial dressings. Simple randomization was followed for the allocation of patients. Outcome parameters were assessed, compiled, and were statistically analyzed. Subjects and Methods: Eighty cases were included in the study, forty in each group. Each group patient underwent dressing with respective allotted topical antimicrobial agent, and outcome parameters were compared. In both groups, Bates-Jensen Wound Assessment Tool (BWAT), Visual Analog Scale (VAS), and Vancouver Scar Scale (VSS) scores were documented. Parameters compared were wound healing, patient acceptability, any adverse events, and quality of the healed scar. Statistical Analysis Used: The data was compiled and analyzed statistically for Outcome parameters will be analyzed for distribution, central tendency, and variability by calculating Mean, SD and p-value using Microsoft excel software (2007). Results: At 21 days, the acetic acid group showed complete reepithelialization in 45% of the cases and complete granulation in 7.5% of the cases, whereas the SSD group showed complete reepithelialization in 32.5% of the cases. The remaining cases in both groups healed after 21 days. BWAT scores were reduced in both groups. Mean VAS and mean VSS scores were comparable in both groups. No adverse event was noted in any group due to respective agent. Conclusions: In our study, we found that 1% acetic acid gel was comparable to 1% SSD in terms of efficacy and is safe to use in partial-thickness burn wounds <20% total body surface area (TBSA) with good clinical outcomes.